Preclinical evaluation of 131I-Bevacizumab – A prospective agent for radioimmunotherapy in VEGF expressing cancers. (May 2017) - Kameswaran, Mythili; Sarma, Haladhar Dev; Dash, Ashutosh
Abstract: This study focuses on preparation and evaluation of 131 I-bevacizumab by Iodogen method for targeting VEGF over-expressing cancers for therapy. 131 I-Bevacizumab exhibited radiochemical purity of 98.0±0.7%. In vitro stability of 131 I-Bevacizumab was retained at >85% in both saline and serum at 37 °C upto 5 days post iodination. In vitro cell studies showed good immunoreactivity and uptake by VEGF expressing tumor cells. Uptake and retention of 131 I-Bevacizumab in tumor with reduction in uptake in presence of cold Bevacizumab confirmed its specificity to VEGF. Highlights: Bevacizumab radiolabeled with 131 I exhibited radiochemical purity of 98.0±0.7%. In vitro stability of 131 I-Bevacizumab retained at >85% upto 5 days post iodination. 131 I-Bevacizumab exhibited immunoreactivity of 80% and good uptake by VEGF expressing cells. Significant uptake and retention of 131 I-Bevacizumab in the melanoma tumor model. Tumor to organ ratio indicate preferential localization of 131 I-Bevacizumab in tumor.